2014
DOI: 10.1080/02626667.2013.841912
|View full text |Cite
|
Sign up to set email alerts
|

Separating baseline conditions from anthropogenic impacts: example of the Damour coastal aquifer (Lebanon)

Abstract: A new structured approach is presented to derive groundwater baseline conditions, in this case for a dolomitic limestone aquifer suffering from salinization and other anthropogenic impacts. It builds on the HydroChemical System Analysis (HCSA) to map different groundwater bodies (hydrosomes) and hydrochemical zones within them, each of which show significant differences in baseline conditions. It also comprises a rigorous elimination scheme for samples affected by bias or pollution. The method is applied to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…According to a survey conducted in 2011, wells within about 350 m from the channel (Figure S3, Supplementary Material) intercept bank-filtrated water as confirmed by δ 18 O (the ratio of oxygen-18 and oxygen-16) and chloride for a mixture of three end-members (river, local rain and infiltrated ocean water). These wells receive > 50% river water contribution (Khadra & Stuyfzand, 2014), summing up to a total discharge of about 3300 m 3 /d, a value that was corroborated by 3-D numerical modeling (Khadra & Stuyfzand, 2018).…”
Section: River Bank Filtrationsupporting
confidence: 58%
“…According to a survey conducted in 2011, wells within about 350 m from the channel (Figure S3, Supplementary Material) intercept bank-filtrated water as confirmed by δ 18 O (the ratio of oxygen-18 and oxygen-16) and chloride for a mixture of three end-members (river, local rain and infiltrated ocean water). These wells receive > 50% river water contribution (Khadra & Stuyfzand, 2014), summing up to a total discharge of about 3300 m 3 /d, a value that was corroborated by 3-D numerical modeling (Khadra & Stuyfzand, 2018).…”
Section: River Bank Filtrationsupporting
confidence: 58%
“…They can explain elevated contents of potential pollutants and possible sources of components in groundwater. Several approaches to groundwater classification and source separation exist (e.g., Khadra and Stuyfzand ; Liesch et al ; Hepburn et al ).…”
Section: Characterization Of Geogenic Backgroundmentioning
confidence: 99%
“…Bivariate statistics, such as correlation analysis, were performed in some studies to reveal the same behavior and thus the origin of trace metals in groundwater (Liesch et al ; Lu et al ). More advanced techniques include multivariate statistics, such as cluster analysis (Flem et al ), factor analysis (Huang et al ), and multicriteria evaluation (Banning et al ; Khadra and Stuyfzand ). According to Hinsby et al (), potential outliers can be identified by, for example, using ionic balance or indicator parameters such as nitrate.…”
Section: Characterization Of Geogenic Backgroundmentioning
confidence: 99%
“…It is a main source of water providing one third of Beirut and its suburbs demands, and has been extensively pumped since 1991 with a total abstraction rate of about 13.5 Mm 3 /year. A description of the hydrogeological setting of this area is available from Khadra and Stuyfzand (2014). Upconing was recorded at different spots.…”
Section: Application To the Damour Aquifer -Lebanonmentioning
confidence: 99%
“…2). Recharge to the aquifer was variable on monthly basis according to rainfall data (Table S2, Supplementary Material) (Meteorological Service 2010) with a 40% infiltration coefficient; chloride concentration of recharge water was assigned a constant value of 30 mg/L as deduced from average chloride in rainfall (11 mg/L) and average evapo-concentration factor in the study area (Khadra and Stuyfzand 2014). Noteworthy that SEAWAT sets the recharge to the uppermost active (wet) layer.…”
Section: Ifk Pumping Layoutmentioning
confidence: 99%